2018
DOI: 10.1007/s42114-018-0044-3
|View full text |Cite
|
Sign up to set email alerts
|

High temperature self-healing SiBCN ceramics derived from hyperbranched polyborosilazanes

Abstract: Self-healing functionality is an important issue of ceramics or ceramic matrix composites used in high temperature and oxidation environment. In this contribution, we reported the cross significant crack self-healing behaviors and mechanism of SiBCN ceramics derived from hyperbranched polyborosilazanes. The self-healing ability of cracks and indention cross sign are enhanced with the increase of oxidation time. And the temperature also influences the healing self-behaviors. The crack healing and indention sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Polymer materials have been used widely in many fields, including energy storage and conversion, 1‐6 electromagnetic interference (EMI) shielding, 7 thermal management, 8,9 sensors, 10,11 cryogenic temperature, 12 carbon dioxide adsorption, 13 solar cell, 14 energy savings, 15 micro/nano‐manufacturing technology, 16 flame retardants, 17 injection molding, 18 coating, 16,19 biomedicine, 20,21 flexible electronics, 21 aerospace, 22 automotive, 22 and defense industries 22 and so forth, due to their lightweight, low cost, low density, easy processing and flexible. However, it is common fact for polymer materials that those composites are extremely easy to be damaged due to the internal or external factors of polymer materials in the process of actual working 23‐27 . These failures would seriously degrade the functionality and lifetime of the devices, resulting in abundant waste, and safety hazards 28,29 .…”
Section: Introductionmentioning
confidence: 99%
“…Polymer materials have been used widely in many fields, including energy storage and conversion, 1‐6 electromagnetic interference (EMI) shielding, 7 thermal management, 8,9 sensors, 10,11 cryogenic temperature, 12 carbon dioxide adsorption, 13 solar cell, 14 energy savings, 15 micro/nano‐manufacturing technology, 16 flame retardants, 17 injection molding, 18 coating, 16,19 biomedicine, 20,21 flexible electronics, 21 aerospace, 22 automotive, 22 and defense industries 22 and so forth, due to their lightweight, low cost, low density, easy processing and flexible. However, it is common fact for polymer materials that those composites are extremely easy to be damaged due to the internal or external factors of polymer materials in the process of actual working 23‐27 . These failures would seriously degrade the functionality and lifetime of the devices, resulting in abundant waste, and safety hazards 28,29 .…”
Section: Introductionmentioning
confidence: 99%
“…At present, once the mobile phone screen is broken, users have to throw it away, which is bound to cause waste, and the application of self-healing materials on the screen will effectively solve this problem. It can be predicted that with the continuous progress of polymer materials design and preparation technology, self-healing materials [128][129][130][131] will also play a key role in the broader field.…”
Section: Discussionmentioning
confidence: 99%
“…Fei Liu et al reported a high‐temperature healing capability of SiCBN through the oxidation process of the ceramic derived from hyperbranched polyborosilazanes at conditions of 1000°C in an air environment as a result of the high content of boron and silicon in the ceramic. Self‐crack‐healing behavior as demonstrated by Fei Liu et al is shown in Figure 3 below 117 :…”
Section: Self‐healing In Ceramics Thin Films and Its Composites/ Comentioning
confidence: 96%
“…These oxides fill the cracks and prevent further damage of the substrate. 91 Nguyen et al studied the self-healing behavior of ytterbium disilicide. In their study, they reported that the composite (Yb 2 Si 2 O 7 -Yb 2 SiO 5 /SiC) has the ability to heal the cracks.…”
Section: Ceramics Thin Films and Its Composites/ Concepts And Previmentioning
confidence: 99%